Taxonomy of the weevil genus Plumolepilius Barrios-Izás & Anderson (Coleoptera: Curculionidae: Molytinae: Conotrachelini): new species from Central America - Barrios-Izás, Manuel A. (Zootaxa, 2020)
Seventeen new species of the genus Plumolepilius Barrios-Izás & Anderson 2016, are described. Images of habitus and genitalia of both sexes are presented, as well as a dichotomous key for the identification of males and females of the known species of the genus. The species included here are P. andersoni Barrios-Izás, new species (Costa Rica and Panamá), P. antonioi Barrios-Izás, new species (Honduras), P. camuna Barrios-Izás, new species (Nicaragua), P. genieri Barrios-Izás, new species (Honduras), P. guaimacaensis Barrios-Izás, new species (Honduras), P. hectori Barrios-Izás, new species (Costa Rica), P. linaresi Barrios-Izás, new species (Honduras), P. maesi Barrios-Izás, new species (Nicaragua), P. molinai Barrios-Izás, new species (Honduras), P. monzoni Barrios-Izás, new species (Guatemala), P. morronei Barrios-Izás, new species (Honduras), P. nelsoni Barrios-Izás, new species (Honduras), P. nicaraguensis Barrios-Izás, new species (Nicaragua), P. obrienorum Barrios-Izás, new species (Costa Rica), P. solisi Barrios-Izás, new species (Costa Rica), P. velizi Barrios-Izás, new species (Honduras) and P. zarazagai Barrios-Izás, new species (Honduras).